Factors associated with the onset of anemia in pregnant mothers Trimester III in Puskesmas Tempino Muaro Jambi - Eprina Intami; Margareta Pratiwi; Matda Yunartha; sri mulyati (HealthCare Nursing Journal, 2024)
The problem faced by the government with the prevalence rate of pregnant women with anemia 37.1%, Anemia in pregnant mothers has a risk of uterine inertia, low birth, miscarriage, uterus atonia, placenta retention, bleeding.In this analytical study using crossectional design with the total population of 87 pregnant women present in Puskesmas Tempino and the total sample of 38 people.The implementation of the research is planned to start in February until March 2024 using data analysis univariat,bivariat and multivariat, with the results of the study obtained pregnant mothers with anemia 17 (44.70%), mother with a history of disease 16 (42.1%), mother with a risk pregnancy distance 14 (36.8%), low socio-economic 23 (60.5%), the mother with high parity 20 (52.6%), the pregnant mother who consumed fedibah tablets 90 tablets 17 (4.7%), from the test results the statistical results obtains there is a relationship between the history of nutritional substance intake, parity, pregnancies distance, disease history and economic with the three trimester pregnant Mother suffering from anemia in Pushmasmas Muaro Jambi 2024.Hope for health care workers to carry out nutritional counselling activities for pregnant mothers.